2023
DOI: 10.3390/biomedicines11010135
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hepatitis B and Related Liver Diseases Are Associated with Reduced 25-Hydroxy-Vitamin D Levels: A Systematic Review and Meta-Analysis

Abstract: Hepatitis B infection is a major public health problem globally leading to chronic liver disease and death, which are influenced by various environmental and host factors including serum 25-hydroxy-vitamin D levels. There is no comprehensive systematic review reporting the association of serum 25-hydroxy-vitamin D levels and different stages of chronic hepatitis B. This study aimed to analyze the association of 25-hydroxy-vitamin D levels in chronic hepatitis B with various determinants and outcomes. A bibliog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…One possible explanation is the link between vitamin D levels and both hepatitis B and AAC. Previous studies have shown that chronic hepatitis B and liver disease are associated with decreased levels of 25-hydroxyvitamin D [25]. Furthermore, low levels of vitamin D have been linked to an increased risk of peripheral arterial disease.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is the link between vitamin D levels and both hepatitis B and AAC. Previous studies have shown that chronic hepatitis B and liver disease are associated with decreased levels of 25-hydroxyvitamin D [25]. Furthermore, low levels of vitamin D have been linked to an increased risk of peripheral arterial disease.…”
Section: Discussionmentioning
confidence: 99%